2011
DOI: 10.1002/jobm.201000119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral supplementation of Lactobacillus reuteri in reduction of intestinal absorption of aflatoxin B1 in rats

Abstract: The goals of this work were to assess the ability of Lactobacillus reuteri to bind aflatoxin B(1) in the intestinal tract and determine its effect on intestinal absorption of the toxin dispensed in either single or multiple doses in a murine model. Male Wistar rats were used, and two experiments were conducted after bacteria were implanted. Experiment one involved a single-oral dose of toxin, and the subsequent flow cytometric analysis of bacteria isolated from the small intestine and treated with specific FIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Similar experiment conducted in rats fed with different doses of aflatoxin (AFB-1) followed by administration with L. reuteri demonstrated significantly lower levels of AFB-1 in the intestine than in the control group. This study demonstrated that probiotic strains can bind to toxin in the intestine and act as a barrier to toxin-induced cell cytotoxicity (Hernandez-Mendoza, González-Córdova, Vallejo-Cordoba, & Garcia, 2011). Besides aflatoxin, ochratoxin, and zearalenone, other fungal toxins such as patulin and fumonisin can also be neutralized by probiotics.…”
Section: Probiotics To Neutralize Toxins In Foodmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar experiment conducted in rats fed with different doses of aflatoxin (AFB-1) followed by administration with L. reuteri demonstrated significantly lower levels of AFB-1 in the intestine than in the control group. This study demonstrated that probiotic strains can bind to toxin in the intestine and act as a barrier to toxin-induced cell cytotoxicity (Hernandez-Mendoza, González-Córdova, Vallejo-Cordoba, & Garcia, 2011). Besides aflatoxin, ochratoxin, and zearalenone, other fungal toxins such as patulin and fumonisin can also be neutralized by probiotics.…”
Section: Probiotics To Neutralize Toxins In Foodmentioning
confidence: 94%
“…Several probiotic strains such as Propionibacterium, L. rhamnosus GG, L. plantarum, L. casei Bacillus species, and E. faecium were demonstrated to bind and neutralize mycotoxins (Danicke & Doll, 2010;Hernandez-Mendoza, Garcia, & Steele, 2009;Hernandez-Mendoza et al, 2011;Khanafari, Soudi, Miraboulfathi, & Osboo, 2007;Niderkorn, Morgavi, Aboab, Lemaire, & Boudra, 2009;Topcu, Bulat, Wishah, & Boyaci, 2010).…”
Section: Probiotics To Neutralize Toxins In Foodmentioning
confidence: 99%
“…Several studies have revealed that these strains can remove a variety of foodborne mutagens, including heterocyclic amines and heavy metals as lead and cadmium (Morotomi and Mutai 1986;Orrhage et al 1994;Terahara et al 1998) and mycotoxins (Line and Brackett 1995;El-Nezami et al 1998;Halttunen et al 2006;Č vek et al 2012;Serrano-Niño et al 2013). Moreover, selected LAB and fermented dairy products have demonstrated anti-mutagenic properties in vitro Cassand et al 1994;Bolognani et al 1997;Hernandez-Mendoza et al 2009a,b) and in vivo (Lidbeck et al 1992;Felton et al 1994;Hernandez-Mendoza et al 2010, 2011. Therefore, the aim of the present study was to assess the ability of 14 lactic acid strains to remove AA in vitro, as an approach to determine the potential protective role of lactic bacteria against the food contaminant AA.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…; Hernandez‐Mendoza et al . , ). Therefore, the aim of the present study was to assess the ability of 14 lactic acid strains to remove AA in vitro , as an approach to determine the potential protective role of lactic bacteria against the food contaminant AA.…”
Section: Introductionmentioning
confidence: 99%
“…First it produces several antimicrobial compounds, useful to treat or prevent infectious diseases, such as: i) reuterin, biosynthesized during anaerobic catabolism of glycerol and active against a broad range of pathogenic microorganisms [1,2] ii) reutericin, a bacteriocin of 2,7 kDa displaying lytic activity [3] iii) reutericyclin, a highly hydrophobic tetramic acid derivative, with a molecular mass of 349 Da exhibiting a broad inhibitory spectrum [4]. Additional antimicrobial features have recently been described in this species like the ability to neutralize toxins produced by fungi [5], to modulate expression of toxins in different bacterial species [6] and to co-aggregate with toxinogenic Staphylococcus aureus [7]. Furthermore L. reuteri displays anti-inflammatory properties linked to a factor secreted by the biofilm-forming cells [8].…”
mentioning
confidence: 99%